Preparation and property evaluation of oral colon targeted protein delivery system with sodium alginate and chitosan - Long Ma; Wentao Zhou; Xizhi Ma; Xiaopo Li; Qian Zhang; Wenting Ma; Nafei Chen; XiaoTao Zhou; XiaoHui Tang (Scientific Reports)
Abstract Oral administration of protein-based biologics faces challenges such as low bioavailability and a short half-life in the gastrointestinal tract. This study focuses on developing a novel encapsulation technique using sodium alginate and chitosan to create nanospheres that efficiently deliver bovine serum albumin, a model protein. Through a combination of single-factor and response surface experiments, optimal preparation conditions were identified, yielding stable nanospheres with high encapsulation rates and small particle sizes. The release of the protein was pH-dependent, with more substantial release under alkaline conditions, resembling the environment of the colon. In vitro safety testing confirmed that the nanospheres had low toxicity and did not induce significant hemolysis or cell death. This approach demonstrates significant potential for enhancing the oral bioavailability of protein-based drugs, overcoming the typical challenges faced by oral drug delivery systems. The developed formulation offers a simple yet effective method for targeted colonic delivery, representing a promising strategy for improving the clinical efficiency of protein biologics.